PELATIHAN DIGITAL MARKETING KARYAWAN SALON UNTUK MENINGKATKAN PENDAPATAN DI SALON JOIS TURANGGA - Nani Suryani; Agus Hasbi Noor; Nunu Mahmud Firdaus (IKIP Siliwangi, 2026)
The beauty salon industry in Indonesia has grown rapidly, encouraging businesses to adapt to the digital era through modern marketing strategies. This study aims to analyze the effectiveness of digital marketing training in improving employees’ competencies and salon income. The research applied a Mixed Method with a Sequential Explanatory Design, combining quantitative pretest–posttest analysis with qualitative interviews and observations. Results show a significant improvement in employees’ abilities after the training. The average pretest score of 52 increased to 76 posttest, accompanied by a 30–50% increase in revenue and improved work efficiency. The SWOT analysis revealed that the main strength lies in enhanced digital skills, while challenges include limited technological infrastructure. Therefore, digital marketing training effectively improves human resource competencies and strengthens business competitiveness.